The development & characteristics of a physical activity questionnaire for epidemiological studies in urban middle class Indians - Bharathi, A V; Sandhya, N; Vaz, M (Indian journal of medical research (New Delhi, India : 1994), 2000)
A single page physical activity questionnaire was designed for use in epidemiological studies. The questionnaire estimates 24 h energy expenditure as well as components of occupation and discretionary leisure time activities. Estimates of physical activity were highly repeatable, when the questionnaire was re-administered within a 4 wk period (e.g., r = 0.86, P < 0.01 for 24 h energy expenditure). Relative validity was assessed by comparing energy intake (using repeated 24 h dietary recalls) and expenditure (using the physical activity questionnaire) over the same period. A correlate of r = 0.33, P < 0.05 between the two measures compared well with reports from literature. The discriminatory power of the questionnaire was assessed by comparing the physical activity patterns of young (18-30 yr) and older (> 60 yr), free living healthy subjects. The questionnaire provides a tool for the assessment of physical activity patterns of urban middle class Indians, which despite its importance has been inadequately studied so far.